Comparative Analysis of Intravenous Ceftriaxone and Ciprofloxacin for the Treatment of Bacterial Peritonitis in Liver Cirrhosis - Syed Asif Raza Zaidi, Wajid Iqbal, Arjan Kumar, Ibadullah Jan, Sheeba Faryal, Rizwan Ahmed, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: This research aimed to evaluate the relative benefits of intravenous ciprofloxacin and ceftriaxone for the treatment of bacterial peritonitis in cirrhotic liver patients. Study Design: Randomized control trial Place and Duration: Department of Gastroenterology, Shaikh Zayed Hospital Lahore in the period from March, 2022 to August, 2022. Methods: Total 130 patients of bacterial peritonitis in liver cirrhosis were included. Patients were undergone for abdomen ultrasound to diagnose liver cirrhosis. Following the acquisition of written informed consent, participants' personal information (such as age, sex, and residence) was meticulously documented. Patients were equally divided in two groups. Group I received intravenous ceftriaxone 1g 12 hourly among 65 patients and 65 cases of group II received ciprofloxacin 200mg 12 hourly for 6 days. Effectiveness among both groups were assessed. Results: There were 44 (67.7%) males and 21 (32.3%) females in group I and in group II 52 (80%) males and 13 (20%) females. Patients mean age in group I was 39.10±6.29 years and in group II mean age was 41.7±3.50 years. We found that majority of the cases were from urban areas 37 (56.9%) in group I and 39 (60%) cases in group II. Frequency of effectiveness in group I was 49 (75.4%) and in group II efficacy found in 47 (72.3%) cases. Post-treatment complications in group I was 7 (10.8%) and in group II found in 6 (9.2%) cases. Satisfaction rate among patients was almost equal 46 (70.8%) and 45 (62.9%) in group I and II. Conclusion: The findings of this research indicate that the administration of ciprofloxacin intravenously is just as effective as the administration of ceftriaxone intravenously for the treatment of spontaneous bacterial peritonitis in cirrhotic cases.